PERAN KEBIJAKAN PUBLIK DALAM MENINGKATKAN DAYA SAING PARIWISATA DI KOTA AMBON PROVINSI MALUKU - KWELJU, JUNUS (JURNAL BADATI, 2019)
This study aims to understand the importance of public policy roles in four indicators of tourism competitiveness according to the World Travel and Tourism Council (WTTC) including Human Tourism Indicator (HTI), Infrastructure Development Indicator (IDI), Social Development Indicator (SDI), and Price Competitiveness Indicator (PCI). An exploratory research method was used to understand the success of tourism public policy in improving the tourism competitiveness in Ambon City. The results found that there was a need of bottom-up policy to encourage the community and private sectors to be creative in producing the expected output. In addition, there was also a need of development policy to provide road access and improve sanitation facilities in touristy destinations so that the community could experience a trickledown effect. Furthermore, policies on creating a balance between the price of commodities consumed and available facilities for the tourists and protecting them from crimes. Therefore, it is expected that the policies issued by the Local Government of Ambon City could improve the tourism competitiveness and community welfare, which simultaneously could increase the Locally-Generated Revenue of Ambon City.